2011
DOI: 10.1111/j.1460-9568.2011.07898.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial feeding synchronizes behavioral, hormonal, metabolic and neural parameters in mother‐deprived neonatal rabbit pups

Abstract: Nursing in the rabbit is under circadian control, and pups have a daily anticipatory behavioral arousal synchronized to this unique event, but it is not known which signal is the main entraining cue. In the present study we hypothesized that food is the main entraining signal. Using mother-deprived pups we tested the effects of artificial feeding on the synchronization of locomotor behavior, plasma glucose, corticosterone, FOS and PER1 protein rhythms in suprachiasmatic, supraoptic, paraventricular and tuberom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 56 publications
(144 reference statements)
1
41
1
1
Order By: Relevance
“…Besides, the diffuse part of the dorsomedial nucleus (DMN; Caba et al, 2008) and parabrachial nucleus (PBN; Juárez et al, 2012) are entrained by the timing of feeding, but not the SCN (Caba et al, 2008), similar to rodents (Mistlberger, 2011). Moreover, we recently demonstrated that food, by artificial feeding, and not other signals from the nursing mother, is sufficient to induce FAA in these subjects (Morgado et al, 2011). In the present experiment, we analyzed FOS expression in these three telencephalic areas at four time points, two before and two after daily nursing.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Besides, the diffuse part of the dorsomedial nucleus (DMN; Caba et al, 2008) and parabrachial nucleus (PBN; Juárez et al, 2012) are entrained by the timing of feeding, but not the SCN (Caba et al, 2008), similar to rodents (Mistlberger, 2011). Moreover, we recently demonstrated that food, by artificial feeding, and not other signals from the nursing mother, is sufficient to induce FAA in these subjects (Morgado et al, 2011). In the present experiment, we analyzed FOS expression in these three telencephalic areas at four time points, two before and two after daily nursing.…”
Section: Introductionmentioning
confidence: 90%
“…Serial sections were collected in PB; every two of four sections were used for labeling of FOS-or FOS and ORX-(FOS/ORX-) immunoreactive (ir) cells, as described below, following protocols previously established in rabbit brain (Caba et al, 2008;Juárez et al, 2012;Morgado et al, 2011). Tissue was washed in PB four times, 5 min each, to remove excess aldehydes, and then exposed for 10 min to a 0.5% hydrogen peroxide solution to eliminate endogenous peroxidase activity.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Entrainment appears to use both food and social cues. The circadian clock can be entrained by artificial feeding through a tube surgically implanted into the stomach (Morgado et al 2011). However, olfactory cues from the dam are also critical, as when fed milk formula by gavage at the same time every day, the pups only anticipate this feeding when it is accompanied by natural or artificial maternal pheromones (Montúfar-Chaveznava et al 2013).…”
Section: Neural Basis Of Anticipation Of Maternal Carementioning
confidence: 99%
“…In addition to the SCN, both clock genes and their proteins in peripheral and central regions are also reset, and shift their oscillations, by stimuli such as stress or periodic feeding (Takahashi et al 2001 ;Morgado et al 2011 ). For this reason, assessment of rhythms of clock genes and their proteins in specifi c areas or nuclei in central and peripheral tissues is commonly used as an index of synchronization by a specifi c stimulus (Feillet et al 2008 ).…”
Section: Photic and Nonphotic Entrainmentmentioning
confidence: 99%